Challenges and Opportunities of Economic Diplomacy for Iranian Businesses in Global Markets - Nikbakht , Ahmad; Pirzad, Ali; Mousavi, Seyed Najm al-Din (Business, Marketing, and Finance Open, 2024)
This study aims to explore the challenges and opportunities of economic diplomacy for Iranian businesses in global markets. Employing a qualitative research design, the study involved semi-structured interviews with 24 participants, including business executives, policymakers, trade experts, and diplomats based in Tehran. Data collection continued until theoretical saturation was achieved, and the transcripts were analyzed using thematic analysis with the aid of NVivo software. The study identified seven key challenges, including political and economic sanctions, bureaucratic inefficiencies, limited diplomatic networks, cultural barriers, high global competition, resource deficiencies, and unstable domestic policies. Conversely, six major opportunities were highlighted, such as Iran’s strategic geographic location, growing domestic industries, the potential for international trade agreements, leveraging cultural diplomacy, technology adoption, and expanding non-oil exports. The findings underscore the dual nature of economic diplomacy as both an obstacle and a tool for fostering international business. Economic diplomacy for Iranian businesses operates within a complex landscape of constraints and possibilities. While sanctions and bureaucratic inefficiencies pose significant hurdles, opportunities such as geographic positioning, regional trade integration, and technology-driven solutions provide pathways for growth. To harness these opportunities, Iranian policymakers and businesses must adopt coordinated governance frameworks, expand diplomatic outreach, and embrace corporate and public diplomacy strategies.